Hidden Impact: Toxic Dinoflagellates Threaten the Sustainability of Pearl Cultivation in Sekotong, West Lombok, Indonesia - Mujib, Abd. Saddam; Dermawan, Awan (Jurnal Biologi Tropis, 2025)
The Sekotong waters, which serve as a pearl aquaculture center, heavily rely on good water quality but face unseen threats that could jeopardize the sustainability of the pearl farming. This study aims to examine the presence and distribution of five major dinoflagellate genera Dinophysis, Gymnodinium, Prorocentrum, Ceratium, and Protoperidinium in the waters of Sekotong, West Lombok, which is both a conservation area and a center for pearl aquaculture. This research is crucial given the potential impacts of harmful dinoflagellates on marine ecosystems and the sustainability of pearl production. Sampling was conducted at four stations, revealing variations in dinoflagellate abundance. Station 1 was dominated by Protoperidinium (approximately 15%), followed by Gymnodinium (around 11%) and Dinophysis (about 15%). At Station 2, only Prorocentrum was observed with an abundance of around 24%, whereas Station 3 was mainly inhabited by Ceratium (15%) and Gymnodinium (13%). Station 4 was characterized solely by Ceratium with a low abundance of approximately 4%. Oceanographic conditions such as temperature, salinity, nutrient levels, and current patterns are believed to influence the distribution and abundance of these dinoflagellates, supporting various ecological strategies including photosynthesis, mixotrophy, and heterotrophy. The presence of toxin-producing genera like Dinophysis and Gymnodinium poses a risk of harmful algal blooms (HABs), which can adversely affect the ecosystem and pearl farming activities. Therefore, the findings emphasize the importance of continuous monitoring and effective management to prevent the negative impacts of these harmful dinoflagellates. This study provides a strong scientific basis to support conservation efforts and enhance the sustainability of pearl aquaculture in Sekotong, a region with significant ecological and economic value.